The cause analysis of benign uretero-ileal anastomotic stricture after radical cystectomy and urinary diversion - Liu, Zhenghong; Zheng, Bin; Hu, Yuqi; Li, Haichang; Qin, Xiaowen; Hu, Xuanhan; Wang, Shuai; Wang, Heng; Zhang, Pu; Wo, Qijun; Sun, Li; Mou, Yixuan; et al. (Frontiers in Oncology, 2022)
Background: Benign uretero-ileal anastomotic stricture (UIAS) is a major complication undergoing radical cystectomy (RC) and ileal orthotopic bladder substitution and it can occur in combination with other complications. But risk factors of patients with UIAS have not been well described. Material and methods：We retrospective reviewed 198 patients treated with RC for bladder cancer from 2014 to 2019 at Zhejiang provincial people’s hospital. Patient demographic and clinical variables were conducted to determine the risk factors associated with UIAS by univariable and multivariate logistic regression analysis. Results: A total of 180 patients into the group standards and in all 360 uretero-ileal anastomosis. Among the above cases, 22 patients developed UIAS, including 10 cases of left UIAS, 9 cases of right UIAS, and 3 cases of bilateral UIAS. There was no difference in demographic, operative, or perioperative variables between patients with and without UIAS. In a multivariate analysis, after adjusting for gender, age, surgical methods, and underlying diseases, intraoperative or postoperative blood transfusion(HR=0.144, P<0.01), postoperative urinary tract infection(HR=3.624, P<0.01), and extracorporeal bladder anastomosis(HR=3.395, P=0.02) significantly increased risk of UIAS. Conclusions: In our date, intraoperative or postoperative blood transfusion, postoperative urinary tract infection and extracorporeal neobladder anastomoses increased the risk of UIAS after radical cystectomy and ileal orthotopic bladder substitution surgery. Further studies with larger samples are necessary to validate this result.